Lhermitte-Duclos Disease: Assessment with MR Imaging, Positron Emission Tomography, Single-photon Emission CT, and MR Spectroscopy - Klisch, Joachim; Juengling, Freimut; Spreer, Joachim; Koch, Donatus; Thiel, Torsten; Büchert, Martin; Arnold, Sebastian; Feuerhake, Friedrich; Schumacher, Martin (American Journal of Neuroradiology, 2001)
Summary: Lhermitte-Duclos disease (LDD) is a rare cerebellar lesion with features of both malformation and benign neoplasm. However, the fundamental nature of the entity, its pathogenesis, and the exact genetic alterations remain unknown. We describe MR findings (including perfusion- and diffusion-weighted images) in two patients with LDD, as well as findings from single-photon emission CT (SPECT), MR spectroscopy (MRS), and fluorodeoxyglucose (FDG) positron emission tomography (PET) that give additional information about tumor pathophysiology. MR imaging usually distinguishes the LDD by its characteristic “tiger-striped” appearance. The regions of increased regional cerebral blood volume (rCBV) within the lesion correlated closely to the regions of FDG-hypermetabolism and high thallium (201-Tl) uptake. Proton MRS revealed an increased level of lactate and decreased level of myo-inositiol and N-acetyl-aspartate, as observed in low-grade gliomas, but decreased levels of choline. Our cases indicate that the functional investigations give additional information about tumor pathophysiology and reflect the histopathologic controversial entity with both characteristics found in low-grade gliomas and characteristics not typical for tumors.